1996
DOI: 10.1017/s0195941700003593
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Evaluation of Respiratory Isolation Rooms in 10 Midwestern Hospitals

Abstract: As a follow-up to a 1992 study of respiratory isolation, we studied compliance with recommendations for respiratory isolation through smokestick testing (1993) and surveys (1994). Effective negative pressure was demonstrated in 80 of 156 rooms and was associated with the presence of anterooms (P<.001). The proportion of surveyed hospitals periodically testing isolation rooms increased from 0% (1992) to 30% (1993) to 100% (1994; P<.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Previous field studies reported that up to 50% of the tested isolation rooms failed to provide a negative pressure [17][18][19][23][24][25]. The main factors that disrupted negative pressurisation included poor reliability of pressurisation control and monitoring devices, strong diffuser flow directed at the door, interaction with other exhaust ventilation systems and poor airtightness of the suspended false ceiling [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous field studies reported that up to 50% of the tested isolation rooms failed to provide a negative pressure [17][18][19][23][24][25]. The main factors that disrupted negative pressurisation included poor reliability of pressurisation control and monitoring devices, strong diffuser flow directed at the door, interaction with other exhaust ventilation systems and poor airtightness of the suspended false ceiling [19].…”
Section: Introductionmentioning
confidence: 99%
“…We carried out field measurements in selected isolation rooms in the new SARS wards between May and August 2005 after a 1.5 years operation to identify factors that affect the ventilation performance. Given the fact that the 558 SARS isolation rooms were designed and constructed nearly at the same time and represented state-of-the-art technologies, it was expected that these isolation rooms would provide better ventilation performance than those reported in the literature [17][18][19][23][24][25]. The current concerns about the risk of an influenza pandemic from avian influenza (H5N1) have made this field study timely as some of these SARS wards are expected to be used by H5N1 patients if one or more human H5N1 cases occur.…”
Section: Introductionmentioning
confidence: 99%
“…9 Further, spaces equipped with anterooms have been shown to more effectively maintain a negative pressure differential than spaces without anterooms. 13 However, critics of anterooms cite a lack of clinical evidence on their effectiveness. There are no published clinical or epidemiologic studies conclusively showing that anterooms diminish or prevent the spread of lab-confirmed airborne infectious human illnesses.…”
Section: Importance Of Aiirs and Anteroomsmentioning
confidence: 99%
“…9 Many studies have indicated that ventilation guidelines are often violated in AIIRs. The negative pressure between the AIIR and corridor was found in 51-91% of AIIRs in the USA [10][11][12][13][14][15][16] but only 32-75% of them followed the minimum pressure difference À2.5 Pa. 15,16 The minimum requirement of 6 ACH was generally achieved in AIIRs but the ACH remained often below the recommendation of 12 ACH. 12,14,16,17 Among Scandinavian AIIRs, the ventilation requirement 12 ACH was achieved in four of six tested AIIRs, as ACHs varied from 5 to 21.…”
Section: Introductionmentioning
confidence: 99%